2015
DOI: 10.2147/ijwh.s48426
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology of premenstrual disorder: informing optimized patient outcomes

Abstract: Premenstrual disorders encompass a spectrum that ranges from mild cyclical psychological and somatic symptoms to the rarer but much-more-severe premenstrual dysphoric disorder. This condition is serious and the etiology is unclear, but possible causes include genetic factors, hormonal fluctuations, and neurotransmitter dysfunctions. Differentiation from other affective disorders can be difficult but is key to providing appropriate management. This comprehensive review will discuss the most-recent classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The prevalence of PMDD is 3%–9%. [3] Similar numbers have been reported from India. In a small, early study of 62 women, Banerjee et al .…”
Section: Prevalencesupporting
confidence: 81%
“…The prevalence of PMDD is 3%–9%. [3] Similar numbers have been reported from India. In a small, early study of 62 women, Banerjee et al .…”
Section: Prevalencesupporting
confidence: 81%
“…It has been reported that markers of anomalous brain substrate, such as left handedness, skeletal asymmetry, or a family history of major mood disorders, are greatly overrepresented in the histories of women with severe, debilitation premenstrual tension syndromes compared with women without premenstrual dysphoric disorder (Hay, Bancroft, & Johnstone, 1994; Klein, Versi, & Herzog, 1999; Robinson & Ismail, 2015). Similarly, this exploratory study suggests an analogous association, by which possession of a familial and/or a personal history of an Axis I mental health disorder, becomes an independent marker of anomalous brain substrate that, by some as of yet unknown mechanism, puts them at increased risk of experiencing intractable emotional disorders triggered by finasteride therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic approach to the diagnosis of PMDD is essential and should include ruling out a premenstrual exacerbation of another underlying or comorbid mood, anxiety or physical disorder. 11,12 .…”
Section: Premenstrual Dysphoric Disorder (Pmdd)mentioning
confidence: 99%